Analisis pengaruh BUMD, Dana Bagi Hasil (DBH) dan PAD terhadap PDRB di kabupaten kota se Provinsi Nusa Tenggara Barat tahun 2018-2024 - Suparlan Suparlan; I Nyoman Pariastana; M. Fauzul Akbar; Nur Arfian Naufan; Tiara Annisa (Universitas Mataram, 2025)
This study aims to analyze the effect of Regional Expenditure, Revenue Sharing Fund (DBH), and Regional Own-Source Revenue (PAD) on the Gross Regional Domestic Product (GRDP) of districts/cities in West Nusa Tenggara (NTB) Province during the 2018–2024 period. GRDP is a key indicator reflecting regional economic performance, making it essential to examine the extent to which fiscal instruments contribute to economic growth. This research employs a quantitative approach using panel data regression. Secondary data were obtained from district/city budget realization reports and publications from the Central Bureau of Statistics (BPS). The results indicate that Regional Expenditure has a positive and significant effect on GRDP, Revenue Sharing Fund (DBH) also has a positive and significant effect, while PAD shows a positive but insignificant effect. Simultaneously, the three variables significantly influence GRDP with a coefficient of determination of 72%. These findings highlight that NTB’s economic growth is largely supported by regional expenditure and DBH, while PAD needs to be strengthened to enhance regional fiscal independence.